ROYALTY PAYMENTS TO THIRD PARTIES FOR THE PURPOSE OF CUSTOMS VALUATION OF IMPORTED GOODS (STUDY OF TAX COURT DECISIONS ON IMPORT DUTIES DISPUTES) - Ardiansyah, Ardiansyah (Transnational Business Law Journal, 2023)
Royalties and license fees in this case are all payments made in connection with, among other things, patent licenses, trademark rights, and copyrights. Costs incurred by importers on royalties must be added to the customs value by the WTO Customs Valuation Agreement. Concerning royalties the problem becomes more complicated when it involves payments to third parties. Legal regulations that do not sufficiently explore this topic often lead to disputes between importers and the government and continue to the court level. The aim in this study is to analyze how the customs rules for royalty payments to third parties related to imported goods and how the attitude of judges in determining the customs value of royalty payments on intellectual property related to imported goods. In conclusion for customs valuation, royalty payments to third parties are added to the actual or supposed price. It is irrelevant to whom the royalties are paid, what matters is that the buyer is obligated to pay royalties as long as the royalty payments relate to the imported goods in question. Of the two Tax Court Decisions on the Tobacco Blend cut filler import case and the Tax Court Decision on the shoe import case, the court decided to include in the customs value the payment of intellectual property royalties to third parties.